2007
DOI: 10.1158/1055-9965.epi-06-0675
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Weight History and Endometrial Cancer Risk by Type of Menopausal Hormone Use in the NIH-AARP Diet and Health Study

Abstract: Obesity and menopausal estrogen therapy are established risk factors for endometrial cancer. However, the joint effects of obesity and menopausal hormone therapy on endometrial cancer risk are incompletely understood. We addressed this issue in a cohort of 103,882 women ages 50 to 71 years at baseline in 1995 to 1996. During a median of 4.6 years, which contributed to a total of 455,304 person-years of follow-up through 2000, 677 cases of endometrial cancer were ascertained. Both baseline body mass index (BMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
76
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 33 publications
20
76
1
Order By: Relevance
“…The association between BMI and risk of endometrial cancer among women who never used HT was linear across the entire range of BMI examined. Although these findings are generally similar to other studies that examined risk among never-users (8,31,34), these studies did not examine the finer strata of normal weight women or the interactions by HT were not obvious (32). In contrast, BMI was not clearly related to endometrial cancer risk among ever E + P users.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The association between BMI and risk of endometrial cancer among women who never used HT was linear across the entire range of BMI examined. Although these findings are generally similar to other studies that examined risk among never-users (8,31,34), these studies did not examine the finer strata of normal weight women or the interactions by HT were not obvious (32). In contrast, BMI was not clearly related to endometrial cancer risk among ever E + P users.…”
Section: Discussionsupporting
confidence: 82%
“…As indicated in a comprehensive review (5), whether the positive relationship between BMI and endometrial cancer exists at lower BMI levels has been unclear. In the European Prospective Investigation on Cancer study (31), obesity (BMI z 30) was associated with increased risk but overweight (BMI, 25-29 versus <25) was not, whereas in the NIH-AARP Diet and Health Study (8), overweight women (BMI, 25-29 versus <25) were at increased risk. Our results for the overweight category were of borderline significance (BMI, 25-29.9; RR, 1.40; 95% CI, 0.99-1.96) compared with healthy weight women (defined as BMI of 22.5-25).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Three studies (33,34,39) stratified analyses according to never versus ever HRT use and the Million Women Study (52) reported the number of cases in women on combined HRT across BMI categories giving an analyzed total cases of 2,253. Associations were stronger for never users compared with ever users of any HRT preparation (Fig.…”
Section: Sources Of Heterogeneitymentioning
confidence: 99%